Proceedings of the IEEE/LEOS 3rd International Conference on Numerical Simulation of Semiconductor Optoelectronic Devices (IEEE
DOI: 10.1109/laweb.2003.1250289
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the development effort of Web projects in Chile

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…It was reported that 15 applications were good, 5 were medium and 2 poor. Finally this study revealed that better estimates can be achieved when more experience with CWADEE [17].…”
Section: Literature Reviewmentioning
confidence: 71%
“…It was reported that 15 applications were good, 5 were medium and 2 poor. Finally this study revealed that better estimates can be achieved when more experience with CWADEE [17].…”
Section: Literature Reviewmentioning
confidence: 71%
“…Of these procedures, four were proposed by practitioners (IFPUG guidelines for Web applications [23], Web-points [11], Web objects [46], internet points [13]). The remaining six were proposed by researchers (OOmFPWeb [3,4], data web points [41], Cândido and Sanches [9], Costagliola et al [15], Fraternali et al [20] and OO-HFP [2]). These measurement approaches are summarized and listed chronologically in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some of the approaches (e.g., Web objects [46], Web-points [11], and internet points [13]) cannot be used in the early stages of the Web development lifecycle since they rely on decisions regarding implementation languages and technologies. Furthermore, some approaches like Web objects [46], Web-points [11], and data Web-points [41] do not use an ISO-standardized measurement method, but rather define new methods of sizing. One disadvantage of this is that the size measured with these approaches is not comparable with the size standards that are currently accepted in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of these approaches is that they cannot be used early in the Web development lifecycle as they rely on implementation decisions. In addition, little systematic evaluation of the proposed FSM alternatives for Web applications has been documented [5] [9] [16].…”
Section: Introductionmentioning
confidence: 99%